Water depths and nitrogen rates on sugarcane growth and dry biomass accumulation - Andrea Raquel Fernandes Carlos Costa; Monalisa Soares Costa; Mário Monteiro Rolim; Gerônimo Ferreira da Silva; Djalma Euzébio Simões Neto; Manassés Mesquita da Silva (Bioscience Journal, 2022)
Irrigation and soil fertilization management are essential agricultural practices that improve the growth and development of sugarcane plants and, consequently, increase their production capacity, which is important for sugar and alcohol productions. In this context, the objective of this work was to evaluate the effect of water depths and nitrogen rates on the growth and dry biomass accumulation of sugarcane plants. The treatments consisted in four water depths (1,498; 1,614; 1,739; and 1,854 mm), five nitrogen rates (0; 20; 40; 80; and 120 kg ha-1) and five evaluation times. The experiment was conducted in a randomized block design with a split-split-plot arrangement and four replications, including the factors water depths, nitrogen rates, and days after planting. The dry biomasses of the plant pointer, leaves and culms, culm diameter, plant height, and number of plants were analyzed. The application of nitrogen increased the sugarcane biomass, mainly the pointer (with leaves) and dry culm biomass, and the number of plants. The highest dry culm biomass accumulation and dry leaf biomass were found at the end of the crop cycle for the treatment with the application of nitrogen rates of 80 and 120 kg ha-1. The increases in water depths applied increased the number of plants per linear meter, but the culm and dry leaf biomass did not happen.